Design of hardware structure for fieldbus protocol conversion - Wang Xuedi; Wang Bo; Shi Guangyi; Yan Wei (Dianzi Jishu Yingyong, 2022)
In view of the coexistence of various fieldbus protocols at present，three principles of bus protocol conversion are proposed based on the analysis of CAN bus protocol,MODBUS bus protocol and HART bus protocol，including bus address conversion principle,bus protocol frame conversion principle and bus error notification conversion. And on the basis of this protocol conversion principle，the hardware architecture of fieldbus protocol conversion is proposed to improve the real-time performance of protocol conversion.